Latest results in breeding winter wheat for resistance to Fusarium Head Blight in the Zagreb BC Institute. - Tomasović, Slobodan; Palaveršić, Branko; Ikić, Ivica; Mlinar, Rade; Šarčević, Hrvoje; Jukić, Katarina; Ivanušić, Tomislav (Plant Breeding and Seed Science, 2011)
Fusarium head blight (Fusarium graminearum Schw.) is one of the most dangerous fungal diseases in wheat production decreasing grain yield up to 50% or more what depends on both environmental factors and genotype. Testing of inoculated artificially new Bc winter wheat lines for their resistance to FHB was the objective of the study. In 2008 and 2009 two and five lines of tested 12 new ones respectively were shown to be more resistant than Sana cultivar used as a standard. Majority of the winter wheat lines exceeded level of resistance standing out by Bc 7 and Bc 1 and Bc Lira variety as the highest yielding variety was registered by CCVR in 2009.